Strengthening the Resilience of The Northern Coastal Area of Sumbawa Island Through Earthquake and Tsunami Disaster Mitigation - Irwan, Irwan; Armawi, Armaidy; Novitasari, Shinta Dewi; Sobaruddin, Dyan Primana (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This research aims to analyze efforts to strengthen the resilience of community areas on the north coast of Sumbawa and Satonda island, Nusa Tenggara Barat Province in efforts to mitigate natural disasters. This research is descriptive qualitative research. Data collection was carried out using non-participatory observation methods, in-depth interviews and documentation aimed at people living on the north coast of Sumbawa Island and Satonda island which directly face the Flores Sea. The research results show that the resilience of the northern coastal area of Satonda Island is classified as vulnerable because the local community does not yet understand the potential for earthquakes and tsunamis and disaster mitigation aspects have not been a priority agenda for the local government. People who live on the coast do not receive socialization and knowledge about natural disaster mitigation. Thus, the resilience of the community area to face natural disasters is still relatively weak, so there is a high risk of negative impacts from these natural disasters